THE ROLE OF THE PERSONALITY OF CUSTOMERS AND REPUTATION THE COMPANY AS THE RESTORATION OF SERVICES ON THE MODEL OF MODERATION VARIABLE: IN THE AUTOMOTIVE INDUSTRY IN INDONESIA - Soleh Hidayat (Business and Entrepreneurial Review, 2014)
This study examined the effect of prior customer experiences on the perceived justice in service recovery through the moderation role of customer personality. In addition, this research examinesperceived justice to satisfaction with service recovery with the moderation role of corporate reputation, as well as satisfaction with service recovery influence the future behavior intentionin form of repurchase intention and positive campaign in the form of free advertising by word of mouth. Respondents in this study are the customers of 4 (four) sole distributor agents (ATPM) with 300 respondents, the analysis technique used is Structural Equation Modeling (SEM) with multigroupanalysis.The results showed that: (1) Prior experience affect the procedural, interactional and informational justice, but has no effect on distributive justice (2) Customer personality moderating reinforced the influence of prior experience on procedural and interactional justice, (3) Perceived justice (distributive justice, procedural justice, interactional justice and informational justice) affect satisfaction with service recovery, (4) Corporate reputation moderating reinforced the influence of distributive, procedural and informational justice on satisfaction with service recovery, but not moderating reinforced the influence of interactional justice on satisfaction with service recovery, (5) Satisfaction with service recovery influence the future behavior intention in form of repurchase intention and word of mouth (WOM).